Critiques of theology German-Jewish intellectuals and the religious sources of secular thought - Ḥotam, Yotam 1968- (SUNY series in contemporary Jewish thought, 2023)
"Argues that the modern practice of critique emerged out of religious traditions and can in many ways be traced back to them"